Improving Higher Order Thinking Skills Through Problem Based Learning with a Scientific Approach - Utomo, Supri Wahyudi; Joyoatmojo, Soetarno; Jutmini, Sri; Suryani, Nunuk (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to describe the effectiveness of the problem-based learning model with a scientific approach to improve higher order thinking skills. The type of research used in this study was quasi-experimental with pre-test and post-test group design. The study was conducted by using one control class and one experimental class. The study was conducted on vocational students with a sample of 64 students consisting of 32 students in experimental class and 32 students in control class. The essay test was used as an instrument for retrieving data. Descriptive analysis and t-test were used to do data analysis. The descriptive test results showed that the average score of HOTS in the control class and experimental class had increased. The results of the t-test showed that there was a significant difference in the score of the pre-test and the post-test in the experimental class, whereas the control class had no significant difference. The conclusion of the results of the study shows that there was a difference between the improvement of higher order thinking skills using conventional models and PBLS models. The PBLS model was able to improve students' Higher Order Thinking Skills.